1992
DOI: 10.1037/0021-843x.101.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent and predictive electrodermal correlates of symptomatology in recent-onset schizophrenic patients.

Abstract: Electrodermal activity and symptomatology were interrelated in a group of 56 male and 13 female recent-onset schizophrenic patients. Electrodermal activity was indexed by the frequency of nonspecific skin conductances responses and the number of trials to habituation of the skin conductance orienting response. Symptomatology was assessed by the Brief Psychiatric Rating Scale (BPRS) on two separate test occasions. The first test occasion was during the inpatient period when psychotic symptoms were prevalent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 32 publications
7
42
1
Order By: Relevance
“…Emphasis has been placed on the relationship between chronic stress, the deleterious effects of cortisol on the hippocampus and prefrontal cortex, and their implications for understanding 'allostatic load' in mental illness [32] . However, recent results favor the idea that the cognitive impairment is the effect of the emotional arousal dysregulation, rather then its cause, as initially hypothesized by Nuechterlein [26][27][28] . Indeed, many cognitive abnormalities associated with schizophrenia [33] -impaired memory [34,35] , lowered sensory gating [36] , selective attention [37] , 'jumping to conclusions' [33] , as well as delusions and hallucinations [38] -are also induced in healthy adults under acute emotional stress [39][40][41] .…”
Section: Schizophrenia -A Disease Of Limbic Dysregulation?mentioning
confidence: 86%
See 2 more Smart Citations
“…Emphasis has been placed on the relationship between chronic stress, the deleterious effects of cortisol on the hippocampus and prefrontal cortex, and their implications for understanding 'allostatic load' in mental illness [32] . However, recent results favor the idea that the cognitive impairment is the effect of the emotional arousal dysregulation, rather then its cause, as initially hypothesized by Nuechterlein [26][27][28] . Indeed, many cognitive abnormalities associated with schizophrenia [33] -impaired memory [34,35] , lowered sensory gating [36] , selective attention [37] , 'jumping to conclusions' [33] , as well as delusions and hallucinations [38] -are also induced in healthy adults under acute emotional stress [39][40][41] .…”
Section: Schizophrenia -A Disease Of Limbic Dysregulation?mentioning
confidence: 86%
“…We hypothesize that symptoms may constitute an end-stage of a cyclic and neurodegenerative process [45] , in which limbic dysregulation (caused by compromised inhibition of the amygdala) leads to hyperarousal [26,46] , leading to hypercortisolemia [47] , leading to neurotoxicity [48] and further degeneration of the inhibitory limbic areas [35] , and thus to further limbic dysregulation ( fig. 1 ).…”
Section: Hypothesis and Our Control Systems Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…For variables such as NS-SCRs and SCL, it may be the state aspects that are of greatest interest for schizophrenia, because~at least in this young, recent-onset population! they may predict short-term outcome in an already symptomatic group~Dawson, Nuechterlein, Schell, & Mintz, 1992! and possibly impending relapse or exacerbation in remitted patients One aspect of the present data of particular interest is the relative stability of different measures of EDA responsiveness to stimuli.…”
Section: Discussionmentioning
confidence: 97%
“…A sympathetic upturn-such as elevated autonomic activation (Dawson et al, 1994), or electrodermal activity levels (Hazlett et al, 1997;Dawson et al, 1992b)-seems to be present pre-symptomatically in as high as 60% of patients. Also, it has been observed that stressful life events and highly critical attitudes toward the patient in the social environment predict relapse , while antipsychotic medication reduces relapse rates.…”
Section: Schizophrenia and The Limbic Dysregulation Hypothesismentioning
confidence: 98%